The External Jugular Vein Used as Recipient Vessel in Head and Neck Free Flap Reconstruction: Outcomes Compared to the Internal Jugular Vein. Issue 1 (January 2019) - Ibrahim, Amir E.; Adelman, David M; Parham, Christopher; Hong, Zhang; Villa, Mark; Chahine, Fadel M.; Ghieh, Fadi M.
Abstract : Background: Contradictory data exists on the success rates of employing the external jugular (EJ) vein as a recipient vessel for venous outflow in free flap head and neck reconstruction compared with the internal jugular (IJ) vein. The authors hereby present a retrospective study of prospectively collected data over a 14-year period. Methods: Five hundred seventy-eight patients underwent 639 free flap head and neck over 14 years. Two hundred seventy-eight free flaps employed the EJ vein as the recipient vessel while 326 free flaps employed the IJ vein. Rates of acute and late complications were compared. Results: There were no differences in rates of complications: flap loss, venous thrombosis, arterial thrombosis, bleeding, hematoma, or infection between the EJ and IJ vein groups. Conclusion: The external jugular vein as a recipient vessel for venous outflow in head and neck free flap reconstruction of postoncologic resection defects is a valid option for both primary reconstructions and secondary surgeries.